P634 Real-world data on the efficacy and safety of vedolizumab therapy in patients with inflammatory bowel disease: a retrospective nation-wide cohort study in Singapore. (25th January 2019) - Gan, A T-M; Chan, W P-W; Ling, K L; Hartono, L J; Ong, D E; Gowans, M; Lin, H; Lim, W C; Tan, M T-K; Ong, J P-L; Schwender, B J; Kong, S C; et al.
Abstract: Background: Real-world clinical data on the use of vedolizumab in patients with inflammatory bowel disease (IBD) is lacking in Asian populations. We aim to report the efficacy and safety outcomes of vedolizumab in a nation-wide cohort in Singapore. Methods: A retrospective nation-wide cohort study of adult IBD patients from the 6 largest local hospitals who completed vedolizumab induction between 2015 and 2018 was conducted. The primary outcome measure was steroid-free clinical remission (SFCR) at 14, 24 and 54 weeks after initiation of vedolizumab therapy. SFCR was defined as complete tapering of steroids with a complete absence of symptoms in Crohn's disease (CD), and a partial Mayo Clinic score <2 in ulcerative colitis (UC). Secondary outcome measures included endoscopic remission as defined by complete absence of ulceration in CD and Mayo endoscopic subscore ≤1 in UC; and normalisation of radiological appearance on CT/MR enterography. Results: Fifty-three patients (28 CD, 25 UC) were included in this study, with 64.2% (34/53) anti-TNF-experienced. In CD, SFCR at Weeks 14, 24 and 54 was 39.3% (11/28), 30.0% (6/20), and 42.9% (6/14), respectively. Endoscopic remission was achieved in 30.8% (4/13) of patients at a median treatment duration of 37 weeks, and radiological remission in 22.2% (2/9) at a median treatment duration of 48 weeks. In UC, SFCR at Weeks 14, 24, and 54 was 68.0% (17/25), 66.7% (14/21), and 80.0% (8/10), respectively. Endoscopic remission was achieved in 35.3% (6/17) of UC patients at a median treatment duration of 31 weeks. Thirteen patients (6 UC, 7 CD) discontinued treatment, as depicted in the Kaplan–Meier survival analysis (Figure 1). Thirty-one adverse events occurred in 25/53 patients (47.2%); 5 (9.4%) were serious adverse events necessitating hospitalisation. Infections were the most common adverse event (37.7%, 20/53), with the majority being upper respiratory tract infections (24.5%, 13/53). Five patients (9.4%) developed gastrointestinal infections; 2 had Clostridium difficile colitis, 2 Campylobacter jejuni gastroenteritis, and 1 Salmonella gastroenteritis. Two patients (3.8%) experienced self-limiting infusion reactions. No malignancies or deaths occurred in our cohort. Conclusions: The real-world experience with vedolizumab in Singapore supports its efficacy and safety in the treatment of IBD, especially in patients with UC.